A Contextualist Approach to Health Economics - John B. Davis; Robert McMaster (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
This paper departs from the standard abstract economics approach to health economics to develop a specifically contextualist approach to the subject emphasizing social and historical circumstances affecting health provision. Following Polanyi, it sees the economy as socially embedded and economic relationships as social relationships. The paper critically examines Grossman's natural science utility maximization explanation of people's demand for health and health care, and advances an alternative social science account using a two-way analysis between micro level social relationships and the macro level organization of health in society. Three significant trends affecting the future of health systems are discussed. The paper closes with comments on the influence of psychology in the form of behavioral economics on the future development of a contextualist approach to health economics.
Keywords: I12; A12; A13; 330; Contextualism; Polanyi; Social Embeddedness; Grossman; Health Systems; Behavioral Economics